Diurnal Variation of Blood Pressure and Arterial Stiffness in Chronic Kidney Disease - Kgs M Yusuf Arief Akbar; Novadian Suhaimi; Zulkhair Ali; Suprapti Slamet; Ian Effendi; Syahpri Putra Wangsa; Deddy Primadona Mulia (HM Publisher, 2023)
Hypertension and chronic kidney disease (CKD) are interrelated public health problems throughout the world. Hypertension accompanied by CKD is mostly difficult to control. Difficulty in controlling blood pressure (BP) is known from changes in the diurnal variation of BP over 24 hours in CKD patients with a pattern of non-dipping and reverse dipping at night and an increase in pulse pressure due to arterial stiffness that occurs in CKD, resulting in a high incidence of nocturnal hypertension and masked hypertension. Nocturnal hypertension in CKD has a significant prognostic risk of increased risk of cardiovascular disease and cause of death. Therefore, guidelines for the management of hypertension strongly recommend that patients with hypertension have blood pressure well controlled at all times, especially to improve hypertension control at night in CKD patients.